A study of drinking water quality in Kota Bharu, Kelantan: a special concern on fluoride content - Muhammad, Nur Shazlina (Universiti Sains Malaysia, 2015)
Fluoride content in drinking water is important for oral health. Appropriate intake of it can help to minimize dental carries (tooth decay) whereas excess of it can lead to other health problems such as dental fluorosis and impaired development of central nervous system (CNS) especially among children. In relation to the fluoride, other main parameters also being measured in order to investigate the relationship that might be present among them. This study was aimed to investigate the level of fluoride content in five water treatment plants (WTP) in district of Kota Bharu, Kelantan. It also aimed to determine the concentration of fluoride content in raw and treated water samples from both surface water and groundwater sources, respectively. In all WTP stations, two sampling points were chosen which are at raw and treated water points. For in-situ analysis, the parameters involved were pH, temperature, free-chlorine and turbidity whereas for ex-situ analysis, the parameters involved were fluoride and ammoniacal nitrogen (NH3-N). All water samples were taken three times in a week for eight weeks. The result obtained was then compared with standard value of drinking water from Ministry of Health, Malaysia (MOH). All the data entry, analysis, and interpretation were done by using Microsoft Office Excel. All bar charts and linear regression was performed using Microsoft Office Excel where coefficient of determination value (R2) was used to measure the regression line that help to determine the closeness of relationship present between variables. Based on bar charts trend and R2 values, it was found that all measured parameters did not influence the fluoride content in water samples. However, the increase of fluoride level after the water being treated was due to other chemicals such as Calcium Hydroxide and Sodium Carbonate that used for pH fixing purpose was detected. Groundwater was noted the higher level of fluoride compared to surface water. However, all the fluoride level was not even reach the minimum requirement set by MOH which it should be between 0.4 to 0.6 mg/L. For raw water samples, the highest R2 values were recorded in three out of five WTP stations for the same parameters of NH3-N against pH. This supported that there was a relationship present between parameters of NH3-N against pH. For treated water samples, two stations recorded the R2 values more that 50% which are for the parameters of temperature against free chlorine and NH3-N against fluoride. However other station shows lower R2 values for those parameters which it cannot support the present of relationship between the parameters. Thus, further study is needed to improve and support the findings. The usage of treated water was recommended in ensuring the safety of public drinking water and fluoridation process also highly recommended to be done as parts of treatment process in all WTP stations as natural occurrence of fluoride still not enough to reach minimum standard of 0.40 mg/L for public drinking water.